Hubungan Budaya Kerja Terhadap Prestasi Kerja Pegawai di Kantor Badan Pertanahan Nasional Kota Padang - Wulandari, Ramadhita; Frinaldi, Aldri (Policy, Law and Political Research Center, 2023)
This study aims to determine the relationship between work culture and employee work achievements at the Padang City National Land Agency. Regarding the study approach that uses quantitative types and with the use of the total sampling method. Meanwhile, the population is all employees who number 81 employees. A questionnaire with four answer choices, namely with a likert scale model, is a research tool used. The relationship between the two variables is then tested using product moment correlation. The results showed that there was a relationship between work culture and work performance at the Padang City Land Office with a positive correlation value of 0.637.